Unsaturated Fatty Acid Intake During Periconception and Incidence of Achieving Pregnancy: A Systematic Review and Meta-Analysis - Gatti, Cintia Romina; Gomez Ribot, Dalmiro; Mariani, Javier; Jawerbaum, Alicia (Frontiers in Physiology, 2021)
Background: Previous studies suggest that maternal diets enriched in unsaturated fatty acids may have a positive effect on pregnancy success. The aim of the present study was to conduct a systematic review and meta-analysis to evaluate whether increased dietary intake of polyunsaturated fatty acids (PUFAs) or monounsaturated fatty acids (MUFAs) during the periconception period has beneficial effects on the achievement of a clinical/biochemical pregnancy in women. Methods: The electronic databases PubMed, Medline and Cochrane Central Register, as well as references in related review articles, were searched to find studies assessing the effects of unsaturated fatty acid dietary intake during the periconception period on the achievement of clinical/biochemical pregnancy in women. Results: For the meta-analysis evaluating the effects of periconceptional diets enriched in PUFAs on clinical/biochemical pregnancy, four articles, providing data on 2121 patients, were included. Periconceptional intake of PUFAs has no significant effects on clinical pregnancy compared to controls, according to both the fixed effects and random effects models (RR = 0.99, 95% CI 0.98 - 1.00). Further secondary analysis considering ω-6 and ω-3 PUFAs separately showed no significant effects on clinical pregnancy compared to controls. On the other hand, for the meta-analysis evaluating the effects of periconceptional diets enriched in MUFAs on clinical/biochemical pregnancy, five articles, providing data on 2473 patients, were included. Periconceptional dietary intake of MUFAs has significant effects on clinical/biochemical pregnancy compared to controls according to the fixed effects model (RR = 1.03, 95% CI 1.01-1.06, p<0.0001) but not to the random effects model, due to heterogeneity. A secondary meta-analysis excluding one study which led to heterogeneity showed significant effects of MUFAs on clinical/biochemical pregnancy compared to controls, according to both the fixed effects and random effects models (RR = 1.03, 95% CI 1.01-1.05, p<0.02). Conclusion: The meta-analysis of published clinical studies supports that diets enriched in MUFAs, although not those enriched in PUFAs, may have a positive effect on pregnancy success. Systematic review registration number (PROSPERO): CRD42021239355